2015
DOI: 10.1080/1943815x.2015.1005105
|View full text |Cite
|
Sign up to set email alerts
|

Role of poverty in fuel choice and exposure to indoor air pollution in Pakistan

Abstract: Indoor air pollution, due to household solid fuel use, is responsible for a significant burden of disease in developing countries. Fuel choice is often associated with household income. However, many other socio-economic and environmental factors also influence the choice of fuel and the resultant indoor air pollution exposure. The aim of this paper is to assess the role of poverty on indoor air pollution in Pakistan through fuel choice. Furthermore, a multinomial logit model has been used to predict the deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 6 publications
3
28
0
Order By: Relevance
“…The study found urban children were at slightly higher risk of death than children from rural areas, which was similar to previous similar studies in Bangladesh and Indonesia [24, 25]; despite the fact that the majority of the households in rural Pakistan rely on solids fuels mainly due to the unavailability of better alternatives [44, 45]. An intervention study in Pakistan investigating indoor particulate matter (PM) concentrations in developing countries reported that PM was considerably higher in urban kitchens as rural kitchens were more ventilated than urban ones [46].…”
Section: Discussionsupporting
confidence: 89%
“…The study found urban children were at slightly higher risk of death than children from rural areas, which was similar to previous similar studies in Bangladesh and Indonesia [24, 25]; despite the fact that the majority of the households in rural Pakistan rely on solids fuels mainly due to the unavailability of better alternatives [44, 45]. An intervention study in Pakistan investigating indoor particulate matter (PM) concentrations in developing countries reported that PM was considerably higher in urban kitchens as rural kitchens were more ventilated than urban ones [46].…”
Section: Discussionsupporting
confidence: 89%
“…Recent Global Burden of Disease analysis indicated that poverty was the single largest contributor to childhood illness in sub-Saharan Africa25 though any association between poverty, education, family size, sanitation and fuel use is complex. In recent work in Pakistan, Nasir et al showed multiple inter-related pathways 26. In Ram et al ’s study in Bangladesh in children aged under 5 years with pneumonia where comparable proportions to our study lived in households using gas (85% vs 86% in Karachi) suggested that improved ventilation and the reduction of overcrowding were the single largest preventable determinants of illness.…”
Section: Discussionsupporting
confidence: 73%
“…This divulges that a 1% change in HH income would decrease the probability of using agricultural crop waste and increase the possibility of using wood for the purpose of cooking. However, [37] divulging that low-income households are highly exposed to indoor air pollution because of using unclean fuel for cooking. Likewise, the coefficient of building type was positively and negatively significant for gas, kerosene, wood and animal dung, respectively.…”
Section: Health Effects On Different Sitesmentioning
confidence: 99%